Предмет: Алгебра, автор: zabivnojded

эуэуэуэуэуэкэкэуэуэуэуэзазааааа

Приложения:

Ответы

Автор ответа: vanessa87
1

Ответ:

Объяснение:

Возведем обе части уравнения в квадрат

(x + 1)* sqrt(x^2 - 24) = (x - 1)^2

Возведем обе части уравнения в квадрат

(x + 1)^2*(x^2 - 24) = (x - 1)^4

x^2(x + 1)^2 - 24(x + 1)^2 = x^4 - 4x^3 + 6x^2 - 4x + 1

x^4 + 2x^3 - 23x^2 - 48x - 24 = x^4 - 4x^3 + 6x^2 - 4x + 1

2x^3 - 23x^2 - 48x - 24 = - 4x^3 + 6x^2 - 4x + 1

6x^3 - 29x^2 - 44x - 25 = 0 


zabivnojded: ятебялюблю
Похожие вопросы